ANALISIS PENGGUNAAN SIKLAMAT DAN TARTRAZIN PADA MINUMAN ES JERUK PERAS DI LINGKUNGAN UNIVERSITAS SUMATERA UTARA TAHUN 2017 - Desy Permatasari Manurung; Evawany Y Aritonang; Jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
Orange juice is a beverage sold in the University of North Sumatra commonly. The existence of orange juice vendor is considered as one of thirst loose that can fulfill vitamins and water needs. On the other hand there are concerns related to the use of inappropriate food additives, including sweetener (cyclamate) and dye (tartrazine). The impacts of short-term use of cyclamate are migraine, memory loss, insomnia, irritation, etc. Intolerant reactions in some body will be produced when tartrazine are consumed. In the long term use, cyclamate   and tartrazine can induce cancer. This research used descriptive observational method. The research was conducted in University of Sumatera Utara area. The data were obtained from cyclamate qualitative analysis using precipitation method and cyclamate quantitatively using thermogravimetric method, while tartrazine was qualitatively tested by chromatographypaper method and quantitatively using thermogravimetric method. The test of both samples will be conducted in the Laboratory of Biochemistry and Food Chemistry, FMIPA USU. The result of the analysis is compared with the quality standard based on regulation from the head of BPOM RI number 4 year 2014 about sweetener as food additives and number 37 year 2013 about dye as food additives. Based on examination results of 8 samples of orange juice, it showed that the orange juice contained cyclamate and tartrazine. The content of cyclamate was above maximum permitted level of 200 mg / kg which was not safe to be consumed. Tartrazine was still below maximum permitted level 70 mg / kg that safe to be consumed. In accordance with these statements, the public is suggested to consume orange juice sold in the University of North Sumatra unregularly. In addition, Vendors are not expected to use inappropriate artificial sweetener above maximum permitted levels as it not only endanger consumers’ health but also break the law. Keywords:orange juice, cyclamate, tartrazine